2023
DOI: 10.1002/14651858.cd013611.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab for induction and maintenance of remission in Crohn's disease

Abstract: Background Vedolizumab blocks inflammatory activity within the gastrointestinal tract. Systematic reviews have demonstrated the efficacy of vedolizumab in ulcerative colitis and inflammatory bowel disease in general. This systematic review and meta‐analysis summarises the current evidence of vedolizumab in the induction and maintenance of remission in Crohn's disease. Objectives To evaluate the benefits and harms of vedolizumab versus placebo for the induction and maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Vedolizumab, a monoclonal antibody that binds the integrin a4b7 heterodimer and blocks its interaction with MAdCAM-1 is another potential option. This prevents leukocyte binding to endothelial surface and its extravasation into inflamed tissue and is proven to be effective in Crohn's disease [57]. A study of its use in 11 patients showed subjective clinical improvement in 7 and mucosal improvement in more than half, but the response was short-lived [58].…”
Section: Treatmentmentioning
confidence: 99%
“…Vedolizumab, a monoclonal antibody that binds the integrin a4b7 heterodimer and blocks its interaction with MAdCAM-1 is another potential option. This prevents leukocyte binding to endothelial surface and its extravasation into inflamed tissue and is proven to be effective in Crohn's disease [57]. A study of its use in 11 patients showed subjective clinical improvement in 7 and mucosal improvement in more than half, but the response was short-lived [58].…”
Section: Treatmentmentioning
confidence: 99%